Anti-microbial Activity of Herbal Plant Extracts - Shivang Tripathi; Vishal Gupta (International Journal of Tropical Medicines, 2024)
The Microbial resistance to major antibiotics due to overuse of them and problem observed rapidly during treatment of infectious diseases having a big challenge in health sector. Recently many researchers have been finding the solutions for come out these problems. There are many photochemical have been available, they have potential antimicrobial property against microbial species which occurs resistance against antibiotics. The present study is therefore an attempt for review on Antimicrobial property of herbal plant extracts obtained by variety of extraction process with variety of solvents in which extract can able to come out. Dried extracts after solvent evaporation employed either alone or in combination with variety of concentrations. Polyherbal extract means use of more than one herbal extract; those combinations have to exert additive effects. Herbal Extracts having options to incorporate into different kind of formulations along with different concentrations evaluated effectively against various numbers of microbial species; they were inoculated into prepared culture medium. The effective zone of inhibition showed and measures it in mm. Some herbal extracts or formulation containing herbal extracts exerts similar inhibition as compare to marketed standard as positive control.
Keywords: Herbal plant extract; Zone of inhibition; antimicrobial property; culture media; drug resistance; extraction method; gel formulation